2017
DOI: 10.1111/caim.12219
|View full text |Cite
|
Sign up to set email alerts
|

The impact of close monitoring on creativity and knowledge sharing: The mediating role of leader‐member exchange

Abstract: We examine the influence of supervisors' close monitoring on employees' creativity and knowledge sharing, both of which are important to the enhanced performance and survival of organizations in this era of uncertainty and change. We also identify the mechanism through which supervisors' close monitoring affects employees' creativity and knowledge sharing. A survey was conducted with military officers in South Korea, among whom supervisor–employee interactions occur daily. A regression analysis of 163 supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 75 publications
(132 reference statements)
2
41
0
Order By: Relevance
“…Previous research has noted the positive effects of empowering leadership on various work‐related outcomes including task performance, organizational citizenship behaviour, voice behaviour and knowledge sharing (Lee et al, ). On the other hand, prior studies have found the negative effects of close monitoring behaviour on creativity and knowledge sharing (Son et al, ). The result of the current study found the negative relationship between close monitoring behaviour and creativity.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous research has noted the positive effects of empowering leadership on various work‐related outcomes including task performance, organizational citizenship behaviour, voice behaviour and knowledge sharing (Lee et al, ). On the other hand, prior studies have found the negative effects of close monitoring behaviour on creativity and knowledge sharing (Son et al, ). The result of the current study found the negative relationship between close monitoring behaviour and creativity.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, closely monitored employees might not be psychologically empowered because they tend to lack a sense of confidence and autonomy in their work. Some studies have found that close monitoring behaviour is negatively related to employee creativity (Son et al, ; Zhou, ). Thus, the research expects the following:Hypothesis Close monitoring behaviour is negatively related to creativity .…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research calls for more investigations of how adverse work conditions steer employees away from positive work behaviours (Boyd et al, 2011;Coelho, Augusto, & Lages, 2011;Pooja et al, 2016). A critical example of a positive work behaviour is the generation of new ideas that improve the current organizational situation, such that they offer novelty and usefulness (Son et al, 2017;Zhou & George, 2001). Employees' engagement in such creative behaviours can be instrumental to both employees and their employer.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…An important path through which employees can contribute to organizational effectiveness is through their creative behaviours (Binyamin & Carmeli, 2010;Castro, Gomes, & de Sousa, 2012;Chen & Kaufmann, 2008;Frederiksen & Knudsen, 2017). Such behaviours generate new ideas that can improve the current organizational situation (Shalley & Gilson, 2004;Son, Cho, & Kang, 2017;Zhou & George, 2001) and offer powerful benefits, such as when they add to the organization's learning capacity (Oltra & Vivas-López, 2013) or the implementation of positive change (Maimone & Sinclair, 2014). Despite these beneficial effects, generating new ideas that improve the status quo can be challenging too, because other organizational members may consider the activities disruptive or threatening to their existing power bases (Hon, Bloom, & Crant, 2014;Zhou & George, 2001).…”
Section: Introductionmentioning
confidence: 99%